2014
DOI: 10.1021/om5002556
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Complexed N2O in Bis(pentamethylcyclopentadienyl) Systems of Zirconium and Titanium

Abstract: Methyl triflate reacts with the metastable azoxymetallacyclopentene complex Cp*2Zr(N(O)NCPhCPh), generated in situ from nitrous oxide insertion into the Zr–C bond of Cp*2Zr(η2-PhCCPh) at −78 °C, to afford the salt [Cp*2Zr(N(O)N(Me)CPhCPh)][O3SCF3] (1) in 48% isolated yield. A single-crystal X-ray structure of 1 features a planar azoxymetallacycle with methyl alkylation taking place only at the β-nitrogen position of the former Zr(N(O)NCPhCPh) scaffold. In addition to 1, the methoxy-triflato complex Cp*2Zr(OMe)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 79 publications
0
10
1
Order By: Relevance
“…The diphenylacetylene complexes of permethyltitanocene and zirconocene react with N 2 O to give azoxymetallacyclopentene complexes (Scheme 14a). 93 Some organometallic samarium complexes are also able to insert N 2 O into metal-carbon bonds. The carbon-metal bond of the latter can be cleaved with a variety of substrates processing acidic protons.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
See 2 more Smart Citations
“…The diphenylacetylene complexes of permethyltitanocene and zirconocene react with N 2 O to give azoxymetallacyclopentene complexes (Scheme 14a). 93 Some organometallic samarium complexes are also able to insert N 2 O into metal-carbon bonds. The carbon-metal bond of the latter can be cleaved with a variety of substrates processing acidic protons.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“…Recently, it was shown that the labile azoxymetallacyclopentene complex can be trapped by reactions with MeO 3 SCF 3 (alkylation of the b-N-atom). 93 The reaction product can be isolated and is stable as a solid if stored at À35 1C. In case of Ti, the initial N 2 O adduct is more stable and can be used for further reactions.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
See 1 more Smart Citation
“…A very selective and general method of oxidising a titanocene centre was published by Andersen and co‐workers, who found that gaseous nitrous oxide is capable of introducing terminal oxido units into permethylated titanocenes [Cp* 2 Ti] 7. Earlier, this principle was also applied for other metallocenes of group 4–6 metals 8,9. Hence, we used this procedure for the synthesis of bridged titanocene oxido complexes that are potential starting materials for the generation of the corresponding dihydroxido species.…”
Section: Resultsmentioning
confidence: 99%
“…Metallacycles have rapidly emerged from laboratory curiosities to important intermediates in catalytic processes and in organic and material synthesis. In this context metallacyclopropenes and metallacyclopentadienes of group 4 metallocenes are readily accessible from the reaction of Cp′ 2 M (Cp′ = (un)­substituted η 5 -cyclopentadienyl) with alkynes or from the reduction of Cp′ 2 MCl 2 in the presence of a suitable alkyne and the resulting metallacycles exhibit unusual intrinsic reactivity. , However, precise stoichiometric control of the added alkyne is usually a prerequisite to prevent the formation of metallacyclopentadienes and thereby to isolate the more strained metallacyclopropenes. However, in contrast to the plethora of group 4 metallacycles, , the chemistry of the corresponding actinide derivatives is underdeveloped . Therefore, thorium, which adopts an intermediate position between group 4 and actinide metals, represents an interesting synthetic target for further investigations, since its electronic ground state of 7s 2 6d 2 relates thorium to the group 4 elements.…”
Section: Introductionmentioning
confidence: 99%